FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN PADA PERUSAHAAN TEXTILE DAN GARMENT GO-PUBLIC DI BURSA EFEK INDONESIA (BEI) - Ayutiya, Selly; Desriani, Neny (Jurnal Manajemen dan Keuangan, 2012)
The purpose of this study was to determine whether a variable is the cost of debt, profit, percentage change in earnings, shareholdersâ equity and company size may affect disclosure in financial statements of the textile and clothing companies listed on the BEI. Disclosure of financial statements to attract attention in this study and used as the dependent variable because of the disclosure of financial statements is a means of public accountability and achievement levels of the venture capital market efficiency. Although the variable cost of debt, profit, percentage change in profit, shareholdersâ equity, and the company size used as independent variables, these variables are part of the sustainability of the company, which can be known through the financial disclosure statements. Use multiple linear regression and t-test analysis with 33 textile and garment companies listed on the BEI as a sample, the results indicate that only shareholdersâ equity that affect the disclosure of financial statements.Keywords : Disclosure, Cost of Debt, Profit, Percentage change in earnings, Shareholders equity, and Company size.